Chemical composition of hydrosol volatiles of flowers from ten Paeonia × suffruticosa Andr. cultivars from Luoyang, China. Issue 20 (23rd September 2021) - Lei, Gaoming; Song, Chaoying; Luo, Yongqiang
Abstract: Hydrosol volatiles from flowers of ten Paeonia × suffruticosa Andr. cultivars were analysed by gas chromatography–mass spectrometry (GC-MS) and GC–flame ionisation detector (GC-FID) for the first time. Fifty components were identified representing 97.6–99.8% of total composition, in which oxygenated compounds (87.4–99.8%) predominated. Hydrosol volatiles of five and two cultivars presented chemotypes of 2-phenylethanol (48.0–79.5%) and 1, 3, 5-trimethoxybenzene (72.8%, 50.2%), respectively. Hydrosol volatiles of 'XYTH' rich in β-citronellol (57.2%) probably represented a newly defined chemotype with β-citronellol percentage over 50%. 'GFCC' hydrosol volatiles presented a balanced profile with 1, 3, 5-trimethoxybenzene (31.9%), β-citronellol (31.5%) and 2-phenylethanol (23.0%). 'LHZL' hydrosol volatiles were distinct from others due to occurrence of 6, 9-heptadecadiene (2.0%), 2-heptanol (1.8%), pentadecane (1.5%), ( Z )-3-nonen-1-ol (1.1%) and geraniol (15.7%). Chemotype characterisation of P. × suffruticosa Andr. hydrosols was of significance considering numerous cultivars of the species and potential applications of the hydrosols. Graphical Abstract: UF0001